Creatively-Gifted Preschooler in Multicultural Environment - Nadiya Lazarovych (Pedagogical Discourse, 2012)
The state of the problem of educational process of children of preschool age is analysed in the article. Importance of development of creative personality of preschool child is grounded, influence of multicultural environment to the mastering of general skills of management creative activity is shown.